P3DB: An Integrated Database for Plant Protein Phosphorylation - Yao, Qiuming; Bollinger, Curtis; Gao, Jianjiong; Xu, Dong; Thelen, Jay J. (Frontiers in Plant Science, 2012)
Protein phosphorylation is widely recognized as the most widespread, enzyme-catalyzed post-translational modification in eukaryotes. In particular, plants have appropriated this signaling mechanism as evidenced by the twofold higher frequency of protein kinases within the genome compared to other eukaryotes. While all aspects of plant protein phosphorylation research have grown in the past 10 years; phosphorylation site mapping using high-resolution mass spectrometry has grown exponentially. In Arabidopsis alone there are thousands of experimentally determined phosphorylation sites. To archive these events in a user-intuitive format we have developed P3DB, the Plant Protein Phosphorylation Database (p3db.org). This database is a repository for plant protein phosphorylation site data, currently hosting information on 32,963 non-redundant sites collated from 23 experimental studies from six plant species. These data can be queried for a protein-of-interest using an integrated BLAST module to query similar sequences with known phosphorylation sites among the multiple plants currently investigated. The paper demonstrates how this resource can help identify functionally conserved phosphorylation sites in plants using a multi-system approach.